Constitutive modeling of γ-irradiated silicone rubber foams under compression and shear loading. (January 2021) - Jia, Dong; Yan, Shunping; Peng, Yunqiang; Wei, Liming; Wang, Luobin; Gao, Yang; Hao, Zhiming; Qiu, Yong; Wan, Qiang
Highlights: Uniaxial compression, simple shear and indentation mechanical behaviors of γ-irradiated silicone rubber foams were investigated. The radiation dose-related linear hardening effects for uniaxial compression, simple shear and indentation have been found. The Hyperfoam model was extended to characterize the mechanical behaviors of irradiated silicone foams. The relationships between the initial shear modulus- and hardening exponent-related parameters with radiation dose have been established. The prediction ability about coupling state of compression and shear for the extended Hyperfoam model has been demonstrated. Abstract: Under the service conditions of nuclear engineering applications, silicone rubber foams should endure radiation of γ rays accompanied by compression and shear loading. In this paper, the Hyperfoam model is extended to characterize the mechanical behaviors of silicone rubber foams under γ-irradiation. After exposing silicone rubber foams to a wide radiation dose range from 0 to 500 kGy at room temperature, uniaxial compression and simple shear tests were carried out to establish the relationships between the model parameters of Hyperfoam model and radiation dose, and indentation tests were performed to verify the extended Hyperfoam model. The linear radiation dose-related hardening properties of the material are derived using the testing results, including the linear increases of the initial shear modulus, and the compression stress and the shear stress for a given strain condition, which result in the linear radiation dose-dependent relationships for the initial shear modulus-related model parameters and the radiation dose-independent hardening exponent-related model parameters of Hyperfoam model. The performances of the extended Hyperfoam model are demonstrated by comparing the fitted material responses with uniaxial compression and simple shear data. And the prediction ability is verified by comparing the simulated results of indentation using the finite element method with the test data. The extended model is capable of characterizing the coupling stress state of compression and shear in the investigated irradiation dose range, which is expected to aid in evaluating the safety of nuclear engineering structures.